DETERMINAN PRICE PERCEPTION, PRODUCT QUALITY, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA ORTUSEIGHT DI KOTA SEMARANG - Sadewa, Ryyo; Sedayu, Agung; Anomsari, Ariati; Putra, Febrianur Ibnu Fitroh Sukono (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
This study aims to evaluate the influence of price perception, product quality, and brand image on purchasing decisions for Ortuseight sports shoes in Semarang City. The research is motivated by the growing competition within the local footwear industry and the evolving consumer behavior that now considers not only functional aspects but also symbolic and emotional values of products. A quantitative approach was employed, using a survey method through the distribution of questionnaires to 150 respondents who had either purchased or shown interest in Ortuseight products. The data were analyzed using multiple linear regression to determine the impact of each independent variable on the dependent variable. The findings reveal that price perception, product quality, and brand image all have a significant and positive effect on purchase decisions. Consumers tend to assess the balance between price and product benefits, evaluate quality based on specifications and durability, and are influenced by brand reputation when making choices. These results highlight the importance for companies to maintain a balance between pricing and quality, while also strengthening brand image—not only in terms of corporate reputation but also in how the product is perceived. This research is expected to offer strategic insights for marketing policy development and serve as a reference for future studies.